2009
DOI: 10.11646/zootaxa.2274.1.4
|View full text |Cite
|
Sign up to set email alerts
|

A new Paracoccus species from Palaearctic region (Hemiptera, Sternorrhyncha, Coccoidea, Pseudococcidae)

Abstract: A new mealybug species, Paracoccus leucadendri sp. nov., is described from Portugal. This is the first record of a Paracoccus species from Europe. It is suggested that its presence in Portugal is the result of a fortuitous introduction with its host plant, Leucadendron sp. (Proteaceae). An identification key is presented to distinguish this new Paracoccus species from other mealybug species reported on Proteaceae in the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…Data followed a non‐normal distribution pattern, but there was absolutely no variation. The colour was green in all N. viridis specimens and specimens of A. hymenocleae , A. lichtensioides and P. hakeae , used as positive controls (Mazzeo et al, 2009; McKenzie, 1967), and not green in specimens of P. marginatus , used as a negative control (Ahmed & Deeter, 2022). Therefore, no nonparametric test or any other statistical test can be applied.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data followed a non‐normal distribution pattern, but there was absolutely no variation. The colour was green in all N. viridis specimens and specimens of A. hymenocleae , A. lichtensioides and P. hakeae , used as positive controls (Mazzeo et al, 2009; McKenzie, 1967), and not green in specimens of P. marginatus , used as a negative control (Ahmed & Deeter, 2022). Therefore, no nonparametric test or any other statistical test can be applied.…”
Section: Methodsmentioning
confidence: 99%
“…The body contents in species of these four genera are reported to appear blue/black at maturity and turn green in KOH (McKenzie, 1967). Recently Mazzeo et al (2009) showed that the haemolymph of Paracoccus leucadendri Mazzeo & Franco, a synonym of Paracoccus hakeae (Williams) (von Ellenrieder et al, 2016), also turns green in 10% KOH (Mazzeo et al, 2009). In this study, we included two species of Amonostherium , A. hymenocleae (Cockerell) (a species found in Arizona), A. lichtensioides (Cockerell) (a species found in California and Colorado) and P. hakeae , (a species intercepted from Hawaii and reported from California, Australia, and Portugal) and tested them along with N. viridis to further examine the reliability of a safer solution and optimal pHs for a field‐based diagnostic kit for N. viridis .…”
Section: Introductionmentioning
confidence: 99%
“…Given the opportunity, some of these species might become important pests of proteas in other regions. An example of this is the mealybug Delottococcus confusus, recorded in Portugal (Leandro et al 2006), which is believed to be of southern African origin (Mazzeo et al 2009). These cases reflect the potential of South African arthropod pests to spread to other protea growing regions.…”
Section: Guild Structuresmentioning
confidence: 99%